(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The new naticid species Euspira magenesi is described and figured. The type-material was recovered from Pliocene deposits exposed along the stream Rio Rosello (Emilia region, Piacenza province) and near Villalvernia (Piedmont, Alessandria province).The small-sized Euspira magenesi is featured by channeled suture, open, rather wide umbilicus and abapically produced aperture. It is an uncommon infralittoral element likely related to ecotones between paleobiocoenoses similar to the modern Mediterranean SFBC and DC.